(1) Solution:- a2 b/a3 c
= b/ac
(2) Solution:- a2 b c/ab2 c
= a/b
(3) Solution:- x3y3z3/x2y2z2
= x y z
(4) Solution:- x2+x/x y +y
= x(x+1)/y(x+1)
= X/y
(5) Solution:- 4a2 b/6a3 b
= 4/6x a2 b/a3 b
= 2/3×1/a
= 2/3a
(6) Solution:- 2a-4ab/1-4b2
= 2a (1-2b)/(1)2– (2b)2
= 2a (1-2b)/(1+2b) (1-2b)
= 2a/(1+2b)
(7) Solution:- 2a+3b/4a2-9b2
= 2a+3b/(2a)2 – (3b)2
= 2a+3b/(2a+3b) (2a-3b)
= 1/2a-3b
(8) Solution:- a2+4a+4
= a2+2a+2a+4/(a)2 – (2)2
= a(a+2)+2 (a+2)/(a+2) (a-2)
= (a+2) (a+2)/(a+2) (a-2)
= (a+2)/(a-2)
(9) Solution:- x2-y2/(x +y)2
= (x +y) (x-y)/ (x +y) (x +y)
= X-y/x +y
(10) Solution:- x2+2x-15/x2 +9x+20
= x2+5x-3×15/x2+5x+4x+20
= X(x+5) -3 (x+5)/x (x-5) +4 (x+5)
= (x+5) (x-3)/(x+5) (x+4)
(11) Solution:- a/b c, d/a c
Denominator b c 8 ac, L.C.M= a b c
Therefore, a/ac = a x a/b c x a
= a2/a b c
And a/ac = a x b/a c x b
= a b/a b c
(12) Solution:- x/p q, y/p r
L.C.M of denominator = p q r
Therefore, x/p q = x X r/p q x r = x r/p q r
y/p r= y X x/p r x q = y q/p q r
(13) Solution:- 2x/3m, 3y/2n
L.C.M of denominator= 6mn
Therefore, 2x/3m = 2xX2n/3mx2n= 4xn/6n
= 3y/2n = 3yx3m/2mx3m= 9my/6mn
(14) Solution:- a/a-b, b/a +b
Therefore, L.C.M of denominator (a +b) (a-b)
Therefore, a/a-b= a x(a +b)/(a-b) (a +b) = a(a +b)/a2 – b2
=> b /a +b = b x(a-b)/(a +b) (a-b) = b(a-b)/a2 – b2
(15) Solution:- x2/a2-2ab, y2/a+2b
Therefore, L.C.M of denominator= (a+2b) (a2-2ab)
= (a+2b) (a-2b)a
Therefore, x2/a2-2ab= x2X(a2+2ab)/(a2-2ab) (a2+2ab)= x2 (a2+2ab)/a (a2-4b2)
=> y2/a+2b= y2xa (a-2b)/(a+2b) (a-2b)a = ay2 (a-2b)/a (a2-4b2)
(16) Solution:- 3/a2-4, 2/a (a+2)
L.C.M, of denomination, = (a2-4) a (a+2)
= a (a+2) (a-2)
3/a2-4 = 3xa/(a+2) (a-2)a
= 3a/a(a2-4)
2/a(a+2) = 2(a-2)/a(a+2) (a-2)
= 2 (a-2)/a(a2-4)
(17) Solution:- a/a2-9, b/a+3
Therefore, a2-9, (a)2 – (3)2 = (a+3) (a-3)
L.C.M of denominator= a (a+3) (a-3)
a/a2-9 = a. 1/(a+3) (a-3) = a/a2 – 9
= b/(a+3) = b(a-3)/(a+3) (a-3) = b(a-3)/a2 -9
(19) Solution:- a/a-b, b/a +b, c/a(a +b)
L.C.M, of denominator = a (a +b) (a-b)
a/ a-b = a x a(a +b) /(a-b) a(a +b)= a2(a +b)/a(a2-b2)
b /a +b= b x a (a-b)/(a +b) x a (a-b) = a b(a-b)/a (a2-b2)
c/a (a +b) = c x(a-b)/a (a +b) (a-b) = c(a-b)/a (a2-b2)
(20) Solution:- 2/x2– x- 2, 3/x2+x-6
= x2-x-2 = (x+1) (x-2)
X2+x-6= (x-3) (x-2)
Therefore, (x+1) (x-2) (x+3)
Therefore, 2/x2-x-2= 2x(x+3)/(x+1) (x-2) x (x+3)
3/x2+x-6 = 3x(x+1)/(x+3) (x-2) (x-1)
No comments:
Post a Comment